Perspektif Surat Yudas terhadap Gnostik - Lukas Yuniarto Chandra (Voice, 2022)
One of the messages conveyed in Jude's epistle is a warning to believers in Asia Minor about the false teachers who infiltrated the church at that time. This is a very serious problem because of the various effects caused by false teachers. Jude gave advice that was delivered in earnest to believers as written in Jude 1:3 “so that you keep fighting to maintain the faith that has been conveyed to the saints.” This condition is still relevant to the current condition of the church, where false teachers infiltrate the church and cause serious problems for the congregation. Therefore, it is significant to identify the characteristics of false teachers, so that God's people are alert and have the right understanding not to be affected by false teachings. It is also important to apply the,gnostic understanding approach and compares it with the characteristics of the false teachers described in the epistle of Jude